26.7k views
0 votes
Plz help!!!
Solve 6 (u - 4) - 8 = -6 (-4u + 6) -2u
Combine like-terms before solving

User Userbb
by
4.9k points

1 Answer

4 votes
Combining like terms:
First do the first part which is 6(u-4)-8, you first distribute 6 to u and -4, 6u-24-8
-24-8=-32, 6u-32
Second part the same thing , distribute -6 to -4u and 6, (negative times a negative equals a positive) 24u-36-2u
24u-2u=22u

Solving:
6u-32=22u-36
Subtract 6u on both sides, -32=16u-36
Add 36 on both sides, 4=16u
Divide 16 on both sides
U=4/16 which is 0.25
User Kahler
by
5.1k points